2022
DOI: 10.3390/ph15040486
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of Allium hookeri Extracts Prepared by Different Methods in Type 2 C57BL/J-db/db Mice

Abstract: This study was conducted to evaluate whether Allium hookeri can control diabetic symptoms. Aqueous extract (AE1: 100 mg/kg BW, AE2: 200 mg/kg BW) and ethanol extract (EE1: 100 mg/kg BW, EE2: 200 mg/kg BW) of A. hookeri were orally administrated to diabetic mice (C57BL/J-db/db) for 8 weeks. The negative (NC) and the positive (PC) control groups were treated with 0.9% saline and metformin (150 mg/kg BW), respectively. Glucose and lipid profile (triglyceride, total cholesterol (TC), LDL-C, and HDL-C) as biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The values of spleen weights were higher in the AHL and AHR groups compared with that of NC group though there was no significant difference in spleen and thymus weights among all groups. Previous study has shown that the administration of aqueous and ethanol AHR extracts increased the spleen weights and NK cell activities, and indicated that they may improve immune system [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of spleen weights were higher in the AHL and AHR groups compared with that of NC group though there was no significant difference in spleen and thymus weights among all groups. Previous study has shown that the administration of aqueous and ethanol AHR extracts increased the spleen weights and NK cell activities, and indicated that they may improve immune system [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of AH extract increased the NK cell activity in immunosuppressed mice. The cytotoxic activity of NK cells significantly increased after exposure to AH extracts [ 46 ]. NK cell activity against Yac-1 was significantly higher in AH groups and it showed similar result to the previous study [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, A. hookeri leaf extracts reduced the liver, heart, epididymal fat, and pancreas weights in obese mice, and a significant difference from the NC group was found in the heart and epididymal fat weights. Aqueous and ethanol extract (100 and 200 mg/kg BW) of A. hookeri leaves showed similar patterns by increasing spleen index and decreasing liver and epididymal fat indexes in type 2 diabetic mice [ 36 ]. A. hookeri root ethanolic extract also decreased liver and epididymal fat weights in high-fat-diet-induced obese mice [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…NK cells are crucial cells of the innate immune system, activated NK cells destroy target cells by receptor-ligand interaction and act an immune response to pathogens entering the body [ 60 ]. Treatment with water and ethanol extracts from A. hookeri increased the NK cell activity in type 2 C57BL/J- db/db mice [ 61 ]. An oral administration of A. fistulosum micus to the older mice activated splenic NK cells [ 54 ].…”
Section: Resultsmentioning
confidence: 99%